Mechanisms of isoniazid and rifampicin-induced liver injury and the effects of natural medicinal ingredients: A review - Zhuang, Xiuping; Li, Li; Liu, Tianyi; Zhang, Rui; Yang, Peimin; Wang, Xin; Dai, Long (Frontiers in Pharmacology, 2022)
Isoniazid (INH) and rifampicin (RFP) are the first-line medications used to treat tuberculosis, and liver injury is their’s major adverse effect. Natural medicinal ingredients prevents and treats liver injury. Natural medicinal ingredients provides distinct benefits in alleviating patients’ symptoms, lowering the liver injury risk, delaying disease progression, and strengthening the body’s ability to heal. This paper summarises the recent research on the mechanisms of INH and RFP-induced liver injury and the effects of natural medicinal ingredients on liver injury. It is believed that INH-induced liver injury mechanisms mainly involve oxidative stress, mitochondrial dysfunction, drug metabolic enzymes, protoporphyrin IX accumulation, endoplasmic reticulum stress, and bile transport imbalance, etc. RFP-induced liver injury is mainly related to cholestasis, endoplasmic reticulum stress and liver lipid accumulation. However, the combined effect of INH and RFP on liver injury risk is still not uncertain. RFP can increase INH-induced hepatotoxicity by regulating the expression of drug-metabolising enzymes and transporters. In contrast, INH can antagonise RFP-induced liver injury by reducing the total bilirubin level in the blood. Sagittaria sagittifolia polysaccharide, quercetin, gallic acid and other natural medicinal ingredients play a protective role on INH and RFP-induced liver injury mainly by enhancing the body’s antioxidant capacity, regulating metabolism, inhibiting cell apoptosis, and reducing the inflammatory response. There are many gaps in the literature on INH and RFP-induced liver injury mechanisms and the effect of natural medicinal ingredients on the prevention and treatment of the liver injury. Thus, further research should be carried out from the perspectives of liver injury phenotype, injury markers, in vitro and in vivo liver injury model construction, and liver-gut axis. This paper comprehensively reviewed the literature on mechanisms involved in INH and RFP-induced liver injury and the status of developing new drugs against INH and RFP-induced liver injury. In addition, this review also highlighted the uses and advantages of natural medicinal ingredients in treating the drug-induced liver injury.